Performance of three generations of Asian redtail catfish Hemibagrus nemurus (Valenciennes, 1840) domestication result of nursery phase one - Irin Iriana Kusmini; Deni Radona (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
In order to the success of domestication programs of Asian redtail catfish is necessary to evaluate the level of change in each generation produced. This study aimed to evaluate the performance of growth and survival rate on three populations from each generation spawned of Asian redtail catfish (G-1, G-2 and G-3). The study was conducted experimentally used completely randomized design (CRD) with 3 treatments and 3 replications from May to July 2017. The origin of the post larvae of Asian redtail catfish was the modified seeds from mass spawning of Asian redtail catfish of Cirata population. G-1 was the population resulted from the spawning of the oldest broodstock, G-2 was a population resulted from spawning of the first generation broodstock and G-3 was the resulted from spawning of the second generation broodstock. Spawning process was conducted in the same time. The age of the seeds was one week old after hatching with total length of 0.8-1.0 cm and body weight of 0.0082 ± 0.0001 g. The Asian redtail catfish seeds were reared in the aquarium with dimension of 70 cm 50 cm x 40 cm and equipped with recirculation system. Each aquarium was stocked seed with a density of 2,000 individual 100 L-1 of water. During rearing process (15 days), fish were fed at satiation with frequency of three times per day. Feed was adjusted to mouth opening of larvae. Initially, larvae on 1 to 7 days of rearing process were fed with artemia and after that fed with tubifex. The result showed that the highest growth and survival rate performance (P<0.05) were obtained in Asian redtail catfish seed (G-3) with a value of 1.64 ± 0.02 cm and 53.42 ± 8.86%, respectively. Postlarvae of Asian redtail catfish from third generaton of domesticated (G-3) can increase fish productivity. Abstrak Dalam mendukung keberhasilan program domestikasi ikan baung perlu dilakukan evaluasi tingkat perubahan setiap generasi yang dihasilkan. Penelitian ini bertujuan untuk mengevaluasi performa pertumbuhan dan sintasan tiga populasi hasil pemijahan setiap generasi (G-1, G-2 dan G-3) ikan baung. Penelitian dilakukan pada bulan Mei-Juli 2017. Penelitian dilakukan secara eksperimental dengan menggunakan rancangan acak lengkap tiga perlakuan dan tiga kali ulangan. Pascalarva ikan baung berasal dari hasil pemijahan tiga generasi (G-1, G-2 dan G-3) ikan baung populasi Cirata. G-1 merupakan populasi hasil pemijahan induk tertua (induk pembentuk), G-2 merupakan populasi hasil pemijahan dari induk generasi pertama dan G-3 merupakan populasi hasil pemijahan dari induk generasi kedua. Proses pemijahan dilakukan dalam waktu yang sama. Pascalarva ikan baung yang digunakan berumur satu minggu setelah penetasan, berukuran panjang 0,8-1,0 cm dan bobot rata-rata 0,0082 ± 0,0001 g. Pascalarva ikan baung dipelihara pada akuarium berukuran 70 cm x 50 cm x 40 cm dan dilengkapi sistem resirkulasi. Setiap akuarium ditebar pascalarva dengan kepadatan 2000 ekor/100 L air. Selama 15 hari pemeliharaan, pascalarva ikan baung diberi pakan sekenyang-kenyangnya dengan frekuensi tiga kali sehari. Pakan yang diberikan disesuaikan dengan bukaan mulut pascalarva ikan baung, pada 1-7 hari pemeliharaan diberi pakan berupa artemia dan selanjutnya diberi pakan berupa cacing tubifex. Hasil penelitian menunjukkan bahwa performa pertumbuhan panjang dan sintasan tertinggi (P<0,05) diperoleh pada pascalarva ikan baung G-3 dengan nilai 1,64 ± 0,02 cm dan 53,42 ± 8,86%. Pascalarva ikan baung G-3 hasil domestikasi mampu meningkatkan nilai produktivitas.